The Economic Value of Candlenut Utilization in the Batudulang Village Forest Area, Batu Lanteh Subdistrict, Sumbawa Regency, West Nusa Tenggara - Apriara, Lisa; Markum, Markum; Setiawan, Budhy (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
This study aims to identify the various uses of non-timber forest products (NTFPs), specifically candlenuts, and to analyze the economic value of candlenuts utilized by the community of Batudulang Village, Batulanteh Subdistrict, Sumbawa Regency, West Nusa Tenggara. The study is expected to serve as a basis for consideration and evaluation for forest managers, enabling them to make informed decisions and establish appropriate policies to improve the management system of the area. This research employs a descriptive method using both qualitative and quantitative approaches. The respondents were determined using a census method, with a total of 23 respondents participating in the study. The results of the study show that the respondents, who are members of the Sumber Alam Business Group (KUB), utilize candlenuts in three forms: whole nuts, shelled nuts (oce), and candlenut oil. The analysis of the economic value of candlenuts utilized by the members of the Sumber Alam KUB reveals that the average annual income per person from whole candlenuts is IDR 19.979.501, from shelled nuts (oce) is IDR 38.250.000, and from candlenut oil is IDR 1,700,000.